Emergency obstetric hysterectomy: a two-year observational study at tertiary care center in Berhampur, Odisha, India - Behera, Ritanjali; Rath, Bibekananda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency obstetric hysterectomy is an unequivocal marker of severe maternal morbidity and, in many respects, the treatment of last resort for rupture uterus, severe postpartum hemorrhage (PPH) and other such life-threatening conditions. In no other gynaecological or obstetrical surgery is the surgeon in as much a dilemma as when deciding to resort to an emergency hysterectomy. On one hand it is the last resort to save a mother’s life, and on the other hand, the mother’s reproductive capability is sacrificed. This study is conducted with an aim to determine the frequency, demographic characteristics, indications, and feto-maternal outcomes associated with emergency obstetric hysterectomy in a tertiary care centre. Methods: We conducted a prospective, observational, and analytical study over a period of two years, from September 2017 till September 2019. A total of 56 cases of emergency obstetric hysterectomy (EOH) were studied in the Department of Obstetrics and Gynecology, MKCG Medical College, Berhampur. Results: The incidence of EOH in our study was 12 following vaginal delivery and 44 following caesarean section. The overall incidence was 56 per 21,128 deliveries. Uterine rupture (37.5%) was the most common indication followed by atonic postpartum hemorrhage (25%) and placenta accrete spectrum (10.7%). The most frequent sequelae were febrile morbidity (25.7%) and disseminated intravascular coagulation (21.4%). Maternal mortality was 17.1% whereas perinatal mortality was 51.7%. Conclusions: A balanced approach to EOH can prove to be lifesaving at times when conservative surgical modalities fail and interventional radiology is not immediately available. Our study highlights the place of extirpative surgery in modern obstetrics in the face of rising rates of caesarean section and multiple pregnancies particularly in urban settings in developing countries.